Helicobacter pylori CagA Protein Negatively Regulates Autophagy and Promotes Inflammatory Response via c-Met-PI3K/Akt-mTOR Signaling Pathway - Li, Na; Tang, Bin; Jia, Yin-ping; Zhu, Pan; Zhuang, Yuan; Fang, Yao; Li, Qian; Wang, Kun; Zhang, Wei-jun; Guo, Gang; Wang, Tong-jian; Feng, You-jun; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Cytotoxin-associated-gene A (CagA) of Helicobacter pylori (H. pylori) is a virulence factor that plays critical roles in H. pylori-induced gastric inflammation. In the present study, gastric biopsies were used for genotyping cagA and vacA genes, determining the autophagic activity, and the severity of gastric inflammation response. It was revealed that autophagy in gastric mucosal tissues infected with cagA+H. pylori strains was lower than the levels produced by cagA−H. pylori strains, accompanied with accumulation of SQSTM1 and decreased LAMP1 expression. In vitro, deletion mutant of cagA gene resulted in increased autophagic activity, and decreased expression of SQSTM1 and cytokines, whereas over-expression of CagA down-regulated the starvation-induced autophagy, and induced more production of the cytokines. Moreover, the production of the cytokines was increased by inhibition of autophagy, but decreased by enhancement of autophagy. Deletion of CagA decreased the ability to activate Akt kinase at Ser-473 site and increased autophagy. c-Met siRNA significantly affected CagA-mediated autophagy, and decreased the level of p-Akt, p-mTOR, and p-S6. Both c-Met siRNA and MK-2206 could reverse inflammatory response. H. pylori CagA protein negatively regulates autophagy and promotes the inflammation in H. pylori infection, which is regulated by c-Met-PI3K/Akt-mTOR signaling pathway activation.